Aproximações entre arquitetura e urbanismo nas intervenções realizadas no hipercentro de Belo Horizonte - Daniel Medeiros de Freitas (2006)
The main objective of the work is the construction of interfaces between architecture and urbanism through the study of relation between urban proposals and local interventions in Hipercentro of Belo Horizonte. For such an initial approach is defined - the common propositor character - and the construction of categories of analysis, in order to systemizethe relation between the formal vocabulary, the attributions of value to this vocabulary and the strategies of dialogue of the intervention with constructed space. In this aspect, urbanism is apprehended from its relation with the figure of the Utopia and the idealization of models, gifts in the analysis and proposal of planning. The architecture, on theother hand, is understood through its paper in the conversion of the space constructed in the idealized urban models. The approach is carried to Hipercentro through two boardings: the evolution of the homogeneity spots, in which if it recognizes the process of transposition of models, and the analysis of five prompt situations, in which if it constructs the urban paper of the intervention. The conclusion identifies in the current process of requalification of the Hipercentro a conflictbetween utopian urban models and, retaking the question of the proximity between the disciplines, show five possible interfaces between architecture and urbanism.